(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with the problems of decentralization in Ukraine, which was launched in 2015 to ensure the effective development of the regions. It is determined that an integral part of the reform is the financial decentralization implementation, which consists in the financial resources transfer and responsibility for the regulatory powers providing from central authorities to the local level. The purpose of the paper is to identify peculiarities of financial decentralization in Ukraine and to assess the compliance of expenditures with their financial support. The article reveals the essence of financial decentralization. An assessment of the financial decentralization level in terms of expenditures decentralization is carried out. The expenditures of local budgets for economic activities, as well as for housing and communal services are analyzed. The calculation of indicators that characterize the transfer payments role in the formation of local budgets financial resources is done, the structure of interbudjet transfers is analyzed. In order to compare the level of expenditure with the sufficiency of their financial support, calculation of decentralization indicators by incomes is given. On the basis of the integrated analysis method, partial indicators of expenditures decentralization, partial indicators of incomes decentralization and an integral index of financial decentralization were calculated. According to the research results were concluded that the level of financial decentralization in Ukraine remains low. Local budgets finance expenditures that are not backed by appropriate financial resources. It was found that significant changes in the direction of strengthening financial decentralization occurred only on the indicator of the local taxes share, while the value of other indicators of income decentralization though began to increase after the beginning of the reform in 2015, but have not yet reached the level of 2013–2014. Proved that changes to the budget and tax legislation, which came into force in 2015, stimulated local authorities to expand their own revenue base, but the increase in the level of local budgets financial decentralization has left in recent years has been moving at a rather slow pace. The obtained results of the conducted analysis made it possible to outline the need for further research in the direction of assessing the trends of regional development in the conditions of financial decentralization in order to scientifically substantiate the conceptual foundations for improving its efficiency.